PERTANGGUNGJAWABAN SELEBGRAM TERHADAP KONSUMEN YANG MEMPROMOSIKAN BARANG DAN JASA DI MEDIA SOSIAL - Wida Suryandini, Dewa Ayu Kade; Putrawan, Suatra (Kertha Semaya : Journal Ilmu Hukum; Vol 8 No 6 (2020), 2020)
This paper aims to know the existent of a regulation in Indonesia which controls Instagram Influencers who advertise products through social media and to explain the responsibility of Instagram Influencers towards the products they promote. This writing uses normative legal research method, which relies on regulations and conceptual approach. Findings revealed that the Press Act Number 40 of 1999 has not regulate the social media advertisements, including Instagram influencers. According to the Broadcasting Act Number 32 of 2002, there is no certain article in this Act which prohibits false advertising. Nevertheless, according to the Food Act Number 18 of 2012, it specifically regulates regarding false or misleading advertisements. Moreover, According to the Government Regulation Number 69 of 1999 on Food Labels and Advertisements, it is prohibited to advertise a product for infants up to 1 (one) year old. Furthermore, In accordance with Article 8 to 17 of the Consumer Protection Act Number 8 of 1999, specifically regulates legal protection. Thus aforementioned articles can be a consideration for Instagram Influencer to receive legal protection. Broadcasting institution is responsible for the content of their adverts. However, broadcasting institution in this context means any types of advertising media, including Instagram Influencers who promoted products through social media. Keywords: Advertisement, Instagram Influencer, Responsibility.